(untitled) (Journal of the College of Basic Education, 2026)
The research examines ’The Metaphorical Meaning of Design Heritage and its Interplay in Interior Design Techniques’ as a cognitive device that recodes inherited branding into measurable operational structures. The proposal is based on the interplay of three layers: visual identity, heritage vocabulary, and technical apparatus, where symbols and motifs are translated into standard modules that interact with material, light, and compositional systems. Perceptual staging is activated through directed light intensity and reading gradients, while tactile comfort and spatial relations systems are controlled by operational indicators such as brand density, brightness differences, recognition time, and orientation errors. The approach relies on digital adaptability and flexible governance that separates a fixed symbolic layer from a variable one, enhancing inclusivity and accessibility and establishing continuous improvement that balances material and energy savings with the symbolic consistency of interior space.